Convergence for a Fixed Point of Evolution Families in Banach Space via Iterative Process - Musharaf Shah; Gul Rahmat; Syed Inayat Ali Shah; Ebenezer Bonyah; Zahir Shah; Meshal Shutaywi (Journal of Mathematics)
In this paper, we present the convergence of Krasnoselskii Mann iterative process for common fixed points of pointwise Lipschitzian evolution family of bounded nonlinear operators on a Banach space ℜ.